Boosting output performance of sliding mode triboelectric nanogenerator by charge space-accumulation effect - Wencong He (Nature Portfolio, 2020)
Improving the output performance of sliding mode triboelectric nanogenerators is a great challenge. Herein, a space charge accumulation effect, based on alternating shielding and blank-tribo areas, is demonstrated and effectively promotes charge density output.